Access to Disparate Soft Matter Materials by Curing with Two Colors of Light. Issue 8 (7th January 2019) - Bialas, Sabrina; Michalek, Lukas; Marschner, David E.; Krappitz, Tim; Wegener, Martin; Blinco, James; Blasco, Eva; Frisch, Hendrik; Barner‐Kowollik, Christopher
Abstract: A platform technology for multimaterial photoresists that can be orthogonally cured by disparate colors of light is introduced. The resist's photochemistry is designed such that one wavelength selectively activates the crosslinking of one set of macromolecules, while a different wavelength initiates network formation of a different set of chains. Each wavelength is thus highly selective towards a specific photoligation reaction within the resist. Critically, the shorter wavelength does not induce ligation of the longer wavelength selective species within the same resist mixture, defined as "wavelength orthogonality." Uniquely, this dual‐color addressable resist system allows generating spatially resolved soft matter materials by simply selecting the curing wavelength, thus constituting a wavelength‐orthogonal multimaterial resist with applications ranging from coatings to 3D additive manufacturing of multimaterial architectures. Abstract : A new class of photoresist consisting of two polymers, which respond in a wavelength‐orthogonal fashion, i.e., each photochemical crosslinking step exclusively responds to a specific wavelength, is pioneered. The innovation enables the spatially resolved fabrication of disparate materials and properties from one photoresist as a function of only the color of light.